Perception on cultural ecosystem services associated with the native forest by a university group of students of pedagogy - Aguilar-Correa, Cristián (2019)
This research aimed to analyze the perceptions that have a group of 15 teachers in initial training regarding the cultural ecosystem services associated with the native forest. The participants were students of the careers of Pedagogy in Basic General Education (generations of 2013, 2014, 2015, 2016), and of Pedagogy in primary education with an honorable mention (the generation of 2017) from the Universidad Católica del Maule-Chile. Two qualitative working techniques used in the study were the focus group and the revised identity drawing. The results showed that in pedagogy students alternative visions coexist with respect to ecosystem services; the participating students relate these services to recycling topics and government institutions. The results also showed the importance that participants assign both to the innumerable benefits and contributions that ecosystem services deliver to human beings and to native forests and their cultural ecosystem services as pedagogical spaces at the service of transversal learning in the development of basic education students.